2017
DOI: 10.3390/land6030049
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios of Vegetable Demand vs. Production in Brazil: The Links between Nutritional Security and Small Farming

Abstract: Abstract:Dietary guidelines urge Brazilians to increase their consumption of raw vegetables. Yet key issues must be tackled by the government and civil society, not only to foster consumers' appetite for healthier food, but more importantly to diminish the gaps between local demand and production, determined by food and land accessibility. We examine whether vegetable production in Brazil meets the demand to provide Brazilians the daily amount of fresh food recommended by the World Health Organization (WHO). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…A previous study reported the highest consumption of roots and tubers in rural areas in the South, Southeast, and Central-West [11]. Although the North's and Northeast's consumption was well below the national average, rural areas exhibited higher consumption, with some areas meeting or exceeding the national average [11]. This study shows a higher intake of tubers among tuber consumers in rural areas for all ve macroregions.…”
Section: Tuber Consumption Across Brazilian Macroregionssupporting
confidence: 43%
See 2 more Smart Citations
“…A previous study reported the highest consumption of roots and tubers in rural areas in the South, Southeast, and Central-West [11]. Although the North's and Northeast's consumption was well below the national average, rural areas exhibited higher consumption, with some areas meeting or exceeding the national average [11]. This study shows a higher intake of tubers among tuber consumers in rural areas for all ve macroregions.…”
Section: Tuber Consumption Across Brazilian Macroregionssupporting
confidence: 43%
“…This study has shown that 55% of the Brazilian population consumed tubers at least on one day over the two-day survey. A previous study reported the highest consumption of roots and tubers in rural areas in the South, Southeast, and Central-West [11]. Although the North's and Northeast's consumption was well below the national average, rural areas exhibited higher consumption, with some areas meeting or exceeding the national average [11].…”
Section: Tuber Consumption Across Brazilian Macroregionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Overall, a meta-analysis of foodshed analyses found a "significant opportunity for food system re-localization across North America" [11], and a nationwide analysis finds that local food systems could provide all of the food needs of most areas of the United States, with the exception of high-density population centers such as the northeastern megalopolis or southern California [12]. Foodshed maps and related land-based assessments are not only of great help for leaders of local food movements in the United States, but also are widely used internationally [13]. For example, Karg et al [14] found that although food provided within the city region assisted the provision of fresh perishable crops, a larger geographical diversity of foodsheds appeared to strengthen the resilience of local food systems in West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, as editors, we would seek to provide some level of synthesis from the findings presented herein, as a contribution to the effort to generate generalized knowledge. However, we find ourselves hampered in this endeavor by two issues that are emblematic of the land change field as a whole.First, while the Special Issue consists of a very small sample of the rapidly growing literature on land change, the contributions nevertheless address a wide array of land systems and focal processes, including agricultural intensification through the lens of telecoupling [16], the socioeconomic impacts of increasing production of a single crop commodity [17], spatial co-occurrence of food insecurity and biodiversity [18], increasing food security through the use of conservation agriculture [19], assessing whether food production can meet future needs [20,21], and developing strategies for modeling land use, food production and trade [22]. Furthermore, the studies address these issues across several continents (i.e., South America, Europe and Asia) and concern varying agricultural systems (i.e., focusing on the production of vegetables or grains, with the latter destined either for direct human consumption or for livestock production).…”
mentioning
confidence: 99%